PELAKSANAAN PERDA NOMOR 10 TAHUN 2008 DALAM MENANGANI PEKERJA SEKS KOMERSIAL (PSK) DI KABUPATEN KENDAL (Studi Kasus Lokalisasi Alaska Desa Kalipuru Kecamatan Patean Kab.Kendal) - Agustin Aviana; Turtiantoro . (Journal of Politic and Government Studies, 2017)
Social problem is an action which is inappropriate with mores in society and it can be harmful for many people. Social problem happens as there is a deviation in society and if there is no resolution to solve it, it will not create a piece in society. One of social problems in Kendal is prostitution. Prostitution is difficult to be solved, and in order to stop PSK is needed preventive, curative, and repressive steps. These steps are expected to decrease the growth of prostitution. The research method used in this study is qualitative approach which uses observation, interview, and library research to collect the data. The participants in this research are Kasi Penegakan Perda Satuan Polisi Pamong Praja Kendal regency, Kasi social service of rehabilitation in Kendal regency, leader of prostitution community in Alaska, and coordinator of peer educator in prostitution community in Alaska. The result of this research shows that in order to press the growth of prostitution in Kendal regency based on regional rules in Kendal regency number 10 year 2008 about the rehabilitation of prostitution, the implementation in Kendal regency is not effective yet as the implementation still gets policing movement. The rest of movements are conducted by social service in Central Java province. If prostitute cannot fulfill the punishment, the prostitute will be released by paying tax to the administrator. The recommendation which can be done for Kendal regency is increasing the quality of human resource in regional united worker (SKPD) which relates to implementation of regulation in Kendal regency number 10 year 2008 about the rehabilitation of prostitution and increasing the communication and coordination among regional united worker (SKPD). Keywords: Social Problem, comersial prostitute, Regional Government Movement